Domesticating democracy : the politics of conflict resolution in Bolivia - Ellison, Susan (Susan Helen) (Book collections on Project MUSE., 2018)
In Domesticating Democracy Susan Helen Ellison examines foreign-funded alternate dispute resolution (ADR) organizations that provide legal aid and conflict resolution to vulnerable citizens in El Alto, Bolivia. Advocates argue that these programs help residents cope with their interpersonal disputes and economic troubles while avoiding an overburdened legal system and cumbersome state bureaucracies. Ellison shows that ADR programs do more than that--they aim to change the ways Bolivians interact with the state and with global capitalism, making them into self-reliant citizens. ADR programs frequently encourage Bolivians to renounce confrontational expressions of discontent, turning away from courtrooms, physical violence, and street protest and coming to the negotiation table. Nevertheless, residents of El Alto find creative ways to take advantage of these micro-level resources while still seeking justice and a democratic system capable of redressing the structural violence and vulnerability that ADR fails to treat.